Fish Species Identification Using the Rhombic Squamation Pattern - Ibáñez, Ana L.; Guerra, Ebenezer; Pacheco-Almanzar, Eloísa (Frontiers in Marine Science, 2020)
The shape of fish scales is, to a considerable degree, species-specific, making it possible to identify species using only one fish scale per specimen. However, to our knowledge, the shape of the rhombic lamination pattern has not been considered to identify species. This study used landmarks and geometric morphometric approaches to address two questions: (1) whether the rhombic lamination pattern of fish scales along the longitudinal axis varies within species and sex and (2) how many fish scales of the rhombic squamation pattern should be considered to obtain an adequate identification. These questions were assessed with a MANCOVA and a cross-validated quadratic discriminant analysis (DA) using the rhombus of one, three, and six scales, and 6, 14, and 26 landmarks, respectively, in order to discriminate between two co-generic species, Mugil cephalus and Mugil curema. Proportions of the total shape variance explained by the total length and the centroid size were 2.3, 11.8, and 10.5% and 4.2, 5.1, and 5.4% for one, three, and six scales, respectively. Thus, analyses were performed on the shape and the form (shape plus size). The MANCOVA and DA analyses were found to be effective in detecting differences in scale pattern shape between species (except in the case of three scales; p = 0.079 for the shape and p = 0.065 for the form), whereas no differences were recorded between size and sex in all cases. Findings indicate that a good identification of species is possible, with no significant differences when using shape or form. The DA provided values of 75.8, 75.0, and 73.4% based on the shape, and of 72.7, 75.8, and 75.0% based on the form, for 1, 3 and 6 scales, respectively. Thus, it is possible to obtain a rapid and reliable identification of species using the rhombus of one scale only without considering the size. This is a useful finding in practical terms since scaling requires data on length. The finding of a suitable discrimination using only the rhombus of one scale raises the possibility of using an ocular adaptor on a camera or mobile phone, allowing many individuals to be easily screened without having to collect scales.